Precision Grinding for Rapid Manufacturing of Large Optics - Tonnellier, Xavier (Cranfield University, 2009)
Large scale nuclear fusion and astronomy scientific programmes have increased the demand for large freeform mirrors and lenses. Thousands of one metre class, high quality aspherical optical components are required within the next five to ten years. Current manufacturing process chains production time need to be reduced from hundred hours to ten hours. As part of a new process chain for making large optics, an efficient low damage precision grinding process has been proposed. This grinding process aims to shorten the subsequent manufacturing operations. The BoX R grinding machine, built by Cranfield University, provides a rapid and economic solution for grinding large off-axis aspherical and free-form optical components. This thesis reports the development of a precision grinding process for rapid manufacturing of large optics using this grinding mode. Grinding process targets were; form accuracy of 1 m over 1 metre, surface roughness 150 nm (Ra) and subsurface damage below 5 m. Process time target aims to remove 1 mm thickness of material over a metre in ten hours. Grinding experiments were conducted on a 5 axes Edgetek high speed grinding machine and BoX R grinding machine. The surface characteristics obtained on optical materials (ULE, SiC and Zerodur) are investigated. Grinding machine influence on surface roughness, surface profile, subsurface damage, grinding forces and grinding power are discussed. This precision grinding process was validated on large spherical parts, 400 mm ULE and SiC parts and a 1 m Zerodur hexagonal part. A process time of ten hours was achieved using maximum removal rate of 187.5 mm 3 /s on ULE and Zerodur and 112.5 mm 3 /s on SiC. The subsurface damage distribution is shown to be "process" related and "machine dynamics" related. The research proves that a stiffer grinding machine, BoX, induces low subsurface damage depth in glass and glass ceramic.